A critical analysis of the curricular landscape of secondary Social Studies across the Deep South since the rise of standardization and accountability with No Child Left Behind - Dodd, Katelyn (My University, 2025)
Social Studies as both a field and subject in K-12 education is nebulous and is constantly changing. Since each state is responsible for their own education system, the result is that how Social Studies (and specifically history) is taught in each state differs. History education has proven to be a way that societies can move beyond their history or a way to control the population and legitimize the current social order. The purpose of this study was to complete a critical discourse analysis in the form of textual analysis of the Social Studies curricular landscape in the Deep South and the changes that have occurred since the rise of accountability and standardization around 2001. This study aimed to find patterns of change within the Deep South, in order to also explore how educational policies have helped shape Social Studies education in the region. This study was an analysis of standards (both historical and current) and legislation (both enacted and proposed) from the five Deep South states. Drawing from critical orientations conceptualizing curriculum and discourse, this critical discourse analysis was to connect both the overt and hidden curriculum in the Deep South with the legislative support that allows it to continue. The research found that In the Deep South, the official knowledge required by the state is biased, focused upon the history of white men, heavily influenced by economic principles, and representative of the geographic location of the states in the Bible Belt. The standards, as supported by legislation both enacted and proposed, emphasize and recreate the current social order that is built upon systems of inequality. With the current political climate and the election of the 47th president, this research is pertinent as standards in conservative-dominant areas, such as the Deep South, are revised and implemented.
Keywords: Standards; Educational policy; U.S. History; Curriculum; Knowledge